Promotional Strategy for Typical Minahasa Tuturuga Seasoned Spaghetti via Social Media - Nuraga, Gloria Yawri; Mononutu, Inggrid Reyvie; Tuwaidan, Altje Ellen; Solang, Jenly (Journal of Multi-Disciplines Science, 2024)
Tuturuga seasoning is one of the typical Minahasa spices in North Sulawesi Province. Furthermore, Spaghetti is a typical food from Italy. This research aims to identify promotional strategies for Tuturuga Seasoned Spaghetti food through social media. This study uses a qualitative method. Data was obtained by observation. The data comes from social media consisting of Instagram, Facebook and WhatsApp. The research results show that the social media platforms effectively used as promotional media are Facebook, WhatsApp, and Instagram. The North Sulawesi Provincial Government needs to support Minahasan spice business actors so that promotion via social media can be carried out effectively and efficiently.